Cohesive Sediment Characterization by Combined Sedimentation and Rheological Measurements - Babatope, B.; Williams, B.R.; Williams, D.J.A. (ASCE, 2020)
JOURNAL OF HYDRAULIC ENGINEERING,VOL. 134, NO. 9.